Cultural convergences in world wine consumption - Dal Bianco, Andrea; Boatto, Vasco; Caracciolo, Francesco (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2022)
This paper addresses the dynamics of world wine consumption over the past 50 years in 26 countries, verifying whether or not there is a macro-tendency towards a common consumption style, despite differences in taxation, economic policies and distribution systems among countries. From an empirical point of view, the σ and β convergence hypotheses were formally tested. Model results confirm the existence of both types of convergences. Per capita consumption of wine first experienced a reduction in differences between countries and then converged toward a central value. "Traditional" countries, with historically high levels of consumption, showed a decrease in wine consumption, while emerging countries with historically lower consumption levels showed an increase. These findings not only provide further support to the theory of international convergence of wine consumption on a volume basis, as already observed by other researchers in the European market, but they also offer support for the theory in major world markets. Furthermore, convergence appears to be happening not only at a quantitative level but at qualitative level as well, and this phenomenon may very well reflect the changing tastes of worldwide consumers towards a generalized structure of wine consumption.